Peran kebijakan deviden dalam hubungan antara ROE, CR, PBV terhadap harga saham - Febriany, Khamidatul; Rahman, Taufikur (Nur Science Institute, 2023)
This research aims to determine the effect of return on equity, current ratio, and price to book value on sharia stock prices in the Jakarta Islamic Index with dividend policy as an intervening variable (Case Study on JII for the 2016-2020 Period). The research used is quantitative, secondary data in the form of financial reports of Sharia companies at JII in 2016-2020. The sample used was ten sharia shares registered with JII for 2016-2020. The analytical method used in this research is path analysis. This research shows that the PBV and Dividend Policy variables influence stock prices in a positive and significant direction. The variables ROE and CR hurt share prices. The Sobel test shows that the Dividend Policy does not mediate the influence of ROE and CR on Share Prices, but the Dividend Policy can mediate the influence of PBV on Share Prices.